Application of digital technique to the spectral analysis of Mandelshtam-Brjllouin scattered light - HORNOWSKI, Tomasz; ŁABOWSKI, Mikołaj (Archives of Acoustics, 1989)
The experimentally recorded Mandelshtam-Brillouin type light scattering function is in general a convolution of the real scattering function and the overall instrumental function, accounting for all the deformations introduced by the measuring arrangement. We propose an algorithm for the numerical deconvolution of the spectrum applicable to the correction of the latter, and the deformation of the parameters of the scattering function. Results obtained when testing the computer program determining the Rayleigh line halfwidth Δ$v_R$, as well as the shift δ$v_MB$, halfwidth Δ$v_MB$ of the Mandelshtam-Brillouin line are given, proving high degree of the effectivity of our numerical method.